Perbedaan Fear of Intimacy antara Dewasa Muda yang Pernah dan Tidak Pernah Diselingkuhi Saat Berpacaran - Riryn Sani; Grace Kilis; Imelda Ika Dian Oriza (Fakultas Psikologi Universitas Pancasila, 2011)
The purpose of this research is to see whether there is a significant difference of fear of intimacy between the adolescents who have ever or never been cheated on by their partner in a relationship. The respondents were adolescents aged 18 to 27 years old, divided into some respondents who having been cheated on (N=100), and the ones who never been in that situation (N=155). All respondents filled out a Fear-of-Intimacy scale questionnaire (Descutner & Thelen, 1991). Total 4 respondents of the two groups were interviewed. Quantitative analysis has shown that there was no significant fear of intimacy difference between those two groups. Additional analysis has found that there was a significant relation among fear of intimacy and relationship status, the number of relationship with love relationship duration when the affair was discovered. The qualitative data has supported the quantitative analysis result.